The Effect of the “Building a Lasting Connection (BLC)” Program on Improving Communication and Increasing Intimacy in Couples About to Marry - Dashti Khavidaki, Shokofe Sadat; Rasouli, Mohsen; Jarareh, Jamshid (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to examine the effectiveness of the Building a Lasting Connection (BLC) program on improving communication patterns and increasing intimacy among couples about to marry. The research employed a quasi-experimental design with a pretest–posttest control group and a follow-up phase. The statistical population consisted of all engaged couples who attended Pars Ravan, Khorshid Farda, and Armaghan-e Zendegi Counseling Centers in Karaj during the last quarter of 2024 and the first quarter of 2025. Using convenience sampling, 40 participants (20 couples) were selected and randomly assigned to an experimental group, which received the six-session Building a Lasting Connection (BLC) intervention, and a control group that received no treatment. Data were collected using the Couple Intimacy Questionnaire (Vonden Broeck & Bertman, 1995) and the Couple Communication Patterns Questionnaire (Christensen & Salaway, 1984). Data analysis was conducted using multivariate analysis of variance with repeated measures (MANOVA) via SPSS version 23. The results revealed that the BLC program significantly increased intimacy and mutual constructive communication while decreasing mutual avoidance and demand/withdraw communication styles in the experimental group compared to the control group (p < .05). Additionally, no significant differences were found between posttest and follow-up scores, indicating that the observed improvements were stable over time. The between-group and within-group analyses showed significant interaction effects of time and group on intimacy and communication variables, confirming the effectiveness and persistence of the intervention’s impact. The findings demonstrate that the Building a Lasting Connection (BLC) program is an effective intervention for enhancing intimacy and improving communication among premarital couples.